(untitled) (Revista Archai, 2016)
This article tries to show how Plato conceived of his own philosophy as the highest form of poetry. In the first section, I briefly analyze in the first section three ancient testimonies (Aristotle, Longinus and Proclus) that already interpreted the Dialogues as a kind of poetry. Moreover, I comment on other modern authors that also recognized the literary aspects of Plato’s philosophy, although for a variety of reasons they never developed methodically this reading. In the second section, I show then how Plato comprehended his philosophy in Phaedon as well as in Phaedrus from an artistic perspective. Finally, I emphasize how his thought, contrary to what is normally believed, cannot be hostile to art.